PENGARUH PELAYANAN ONLINE TERHADAP KEMUDAHAN WAJIB PAJAK MEMBAYAR PBB DI KOTA TANGERANG - Adwin Safarudin; MD. Sukamto (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The problem in this research is to see the effect of online services on the ease of taxpayers in paying land and building taxes in Tangerang City. Meanwhile, the aim is to prove the research hypothesis. Online services as an independent variable are measured using service principles, namely Transparency, Accountability, Conditionality, Participation, Equality of Rights, and Balance of Rights and Obligations. Meanwhile, the convenience of taxpayers is used as a dependent variable with the dimensions of ease in submitting Tax Returns Due, ease in paying, Compliance in calculations and ease in payment and arrears. Quantitative research methods were used to answer research problems using a research sample size of 100 respondents who were land and building tax payers in Tangerang City, taken randomly. Based on the results of the research analysis, information can be obtained related to testing the hypothesis, namely that there is a significant influence of online services on the ease of taxpayers in paying for land and buildings. The Tangerang City Regional Revenue Agency, as the provider of Land and Building Tax services, needs to provide outreach regarding the understanding of taxation to the public in Tangerang City, especially regarding the provisions relating to Land and Building Tax